Liquid-phase Hydrogenation of Phenol to Cyclohexanone over Supported Palladium Catalysts - Lihui Fan; Luyang Zhang; Yanming Shen; Dongbin Liu; Nasarul Wahab; Md Mahmud Hasan (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
The ZSM-5, g-Al2O3, SiO2 and MgO supported Pd-catalysts were prepared for the phenol hydrogenation to cyclohexanone in liquid-phase. The natures of these catalysts were characterized by XRD, N2 adsorption-desorption analysis, H2-TPR, CO2-TPD and NH3-TPD. The catalytic performance of the supported Pd-catalyst for phenol hydrogenation to cyclohexanone is closely related to nature of the support and the size of Pd nanoparticles. The Pd/MgO catalyst which possesses higher basicity shows higher cyclohexanone selectivity, but lower phenol conversion owing to the lower specific surface area. The Pd/SiO2 catalyst prepared by precipitation gives higher cyclohexanone selectivity and phenol conversion, due to the moderate amount of Lewis acidic sites, and the smaller size and higher dispersion of Pd nanoparticles on the surface. Under the reaction temperature of 135 oC and H2 pressure of 1 MPa, after reacting for 3.5 h, the phenol conversion of 71.62% and the cyclohexanone selectivity of 90.77% can be obtained over 0.5 wt% Pd/SiO2 catalyst. Copyright © 2016 BCREC GROUP. All rights reservedReceived: 7th March 2016; Revised: 13rd May 2016; Accepted: 7th June 2016How to Cite: Fan, L., Zhang, L., Shen, Y., Liu, D., Wahab, N., Hasan, M.M. (2016). Liquid-phase Hydrogenation of Phenol to Cyclohexanone over Supported Palladium Catalysts. Bulletin of Chemical Reaction Engineering & Catalysis, 11 (3): 354-362 (doi: 10.9767/bcrec.11.3.575.354-362)Permalink/DOI: http://doi.org/10.9767/bcrec.11.3.575.354-362